Epidemiological insights into complication and outcomes in corneal refractive surgery population: findings from KNHANES 2010–2012 - Joon Yul Choi; Sun Young Ryu; Tae Keun Yoo (BMC Ophthalmology)
Abstract Purpose Epidemiological studies on corneal refractive surgery remain limited, particularly regarding complications such as dry eye disease and refractive error regression, which impact long-term visual outcomes and patient satisfaction. This study aimed to evaluate the demographic and clinical characteristics of individuals with a history of corneal refractive surgery using data from the Korean National Health and Nutrition Examination Survey (KNHANES) 2010–2012. Methods This cross-sectional study included 595 participants with a self-reported history of corneal refractive surgery. Data on diagnosed dry eye disease, dry eye symptoms, and previous ocular surgeries were collected through structured questionnaires, while ophthalmologic examinations provided information on refractive errors, intraocular pressure, and other ocular conditions. Logistic regression analysis identified factors associated with dry eye disease and symptoms. Results Dry eye disease and refractive error regression were frequently reported among individuals with a history of corneal refractive surgery. Among participants, 24.2% reported diagnosed dry eye disease, and 33.1% reported dry eye symptoms. Significant myopia (≤ -0.75 D) and significant astigmatism (≤ -0.75 D) were present in 49.4% and 39.7%, respectively. Using the timing of the last ophthalmologic examination as a proxy for time since surgery, results showed a progressive myopic shift in spherical refractive error over time, while the prevalence of dry eye disease and symptoms gradually declined. Female sex (OR = 1.76, 95% CI = 1.05–2.96) and prolonged sun exposure (> 5 h/day, OR = 2.47, 95% CI = 0.96–6.36) were associated with a higher likelihood of diagnosed dry eye disease, while a longer time since surgery was associated with decreased dry eye symptoms. Severe diseases such as cataracts (0.3%), glaucoma (0.5%), and surgically treated retinal disorders (0.2%) were rare. Conclusions This study provides epidemiological insights into associations between corneal refractive surgery and postoperative outcomes, highlighting dry eye disease and refractive error regression as prevalent findings, while observing that severe complications were rarely reported. Sex and sun exposure were identified as important risk factors for dry eye disease, warranting attention in preoperative counseling and postoperative care. These findings support the need for procedure-specific, longitudinal research to optimize patient outcomes and satisfaction.